Provenance Analysis from Lemat Formation in Lubuk Lawas and Lubuk Bernai Areas, Jambi Subbasin, Jambi Province - Daryono, Sapto Kis (Journal of Earth and Marine Technology (JEMT), 2024)
The study of the sedimentary rocks from the Lemat Formation in Bukit Tigapuluh, particularly in the Lubuk Lawas and Lubuk Bernai Areas, aims to clarify and provide an overview of the formation’s history and the evolution of Paleogene stratigraphy within the Jambi Subbasin. Provenance analysis was concluded using petrographic analysis to determine the classification of sandstone types, source rock characteristics and tectonic order. Sandstones in the Lubuk Lawas and Lubuk Bernai areas are classified into Lithic arkose, arkosic, subarkose, felspathic litharenite, silty claystone, sublitharenite and subarkosic wacke. Petrographic data revealed that these sandstones originated from a tectonic setting within the recycled orogenic zone, with sub-zones varying between quartzose recycled, transitional recycled and mixed. This variation indicates a combination of primary source rocks and recycled orogens. Paleocurrent data derived from the sedimentary structures of sandstones in the Lubuk Bernai area suggest deposition directions from the southwest and southeast.